Konflik Dan Integrasi Umat Beragama Dalam Budaya Lokal Di Loka Muksa Sri Aji Joyoboyo Menang Pagu Kediri - Khoiro Ummatin Ummatin (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2017)
The local traditional ritual of 1st of Syura in Loka Muksa Sri Aji Joyoboyo Menang Pagu Kediri in East Java, is a tradition that is held in honor of their ancestors, which is inseparable from the figure of Sri Aji Joyoboyo. This tradition remains as proand contrain the community.Data from this research shows that the implementation of the 1st of Syuraritual in LokaMuksa Sri Aji Joyoboyo with a complete procession of offerings, ritual behavior, and certain preconditions, negative reactions from a number of people who cannot accept the syura local traditions. They are originally from the modern NU group, the Muhammadiyah elite, and the Salafi congregation. They are concurrently establishing legitimate truth to their people, hen the activities concerning the 1st of Syura in Loka Muksa Sri Aji Joyoboyo have the potential to become an open conflict, if they were not managed properly.